Sertipikat Tanah VS Sertifikat Tanah: Analisis Data Penggunaan Istilah Produk Hukum di Media Sosial - Ridho Darman (Journal Islamic Global Network for Information Technology and Entrepreneurship, 2024)
The land title (in Indonesian: sertipikat) is a legal product issued by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency, while “sertifikat” (spelled with 'f' instead of 'p'), which is the standard term according to KBBI (Indonesian Dictionary). The number of social media users increases every year, resulting in a growing amount of data generated. Big data derived from social media can encompass public perception or societal behaviors. The significant benefits derived from social media analytics provide opportunities to explore and analyze data sources within social media. This study analyzes data from the social media platforms Twitter, Facebook, and Instagram to determine common terms used by the public regarding "sertipikat tanah" (land certificate) and "sertifikat tanah" (land certificate). These platforms were chosen because they provide open data. The use of uncommon terms among the public potentially hinders the government's intended objectives. The final results indicate that despite "sertipikat" being the official legal term, the public is more accustomed to using "sertifikat tanah." The comparison of usage between "sertipikat tanah" and "sertifikat tanah" on Facebook is 11% : 89%, on Instagram 38% : 62%, and on Twitter 70% : 30%, with the majority of "sertipikat tanah" usage on Twitter originating from government accounts.